Antibiofilm Activity of Dendrophthoe falcata against Different Bacterial Pathogens - Karthikeyan, Alagarsamy; Rameshkumar, Ramakrishnan; Sivakumar, Nallusamy; Al Amri, Issa S.; Karutha Pandian, Shunmugiah; Ramesh, Manikandan (Planta Medica, 2012)
Dendrophthoe falcata is a hemiparasitic plant commonly used for ailments such as ulcers, asthma, impotence, paralysis, skin diseases, menstrual troubles, pulmonary tuberculosis, and wounds. In this context, the validations of the traditional claim that the leaf extract of D. falcata possesses antibiofilm and anti-quorum sensing activity against different bacterial pathogens were assessed. The bacterial biofilms were quantified by crystal violet staining. Among the 17 bacterial pathogens screened, the methanolic fraction of the leaf extract clearly demonstrated antibiofilm activity for Proteus mirabilis, Vibrio vulnificus, Aeromonas hydrophila, Shigella sonnei, Chromobacterium violaceum ATCC 12472, Vibrio parahaemolyticus, Vibrio harveyi, Vibrio alginolyticus, Vibrio cholerae, and Proteus vulgaris. At biofilm inhibitory concentrations, biofilm formation was reduced by up to 70–90 %. Furthermore, the potential quorum-sensing activity of the leaf extract was tested by agar well diffusion using Chromobacterium violaceum (ATCC 12472 & CV O26) reporter strains. The inhibition of violacein production may be due to direct or indirect interference on QS by active constituents or the interactive effect of different phytocompounds present in the extracts. This is the first report on antibiofilm and QS activity of D. falcata leaf extracts, signifying the scope for development of complementary medicine for biofilm-associated infections.
Keywords: Dendrophthoe falcata; Loranthaceae; biofilm; quorum sensing; bacterial pathogens; confocal laser scanning microscopy